2022
DOI: 10.1177/09544089221111584
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of hydroxyapatite powder mixed electric discharge machining process to improve modified surface features of 316L stainless steel

Abstract: Traditional methods for producing 316L steel with a desired roughness and a uniform thin coating for sufficient bioactivity and long-term durability are highly difficult and require post-processing. Electric discharge machining (EDM) is a nontraditional process that can accomplish both machining and coating the surface concurrently. This study provides a thorough examination of the impacts of EDM process parameters on the machining responses, which are significantly necessary for processing 316L steel to reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The influence of various process parameter on the TWR was depicted in the figure 3. The TWR increases with raise in current, generated spark removes material from the work piece as well as tool material [33]. At higher current owing to the high intensity, it erodes high quantity of materials from the electrodes, results in increase in TWR.…”
Section: Influence Of Various Process Parameters On the Twr Of Incone...mentioning
confidence: 99%
“…The influence of various process parameter on the TWR was depicted in the figure 3. The TWR increases with raise in current, generated spark removes material from the work piece as well as tool material [33]. At higher current owing to the high intensity, it erodes high quantity of materials from the electrodes, results in increase in TWR.…”
Section: Influence Of Various Process Parameters On the Twr Of Incone...mentioning
confidence: 99%
“…Rouniyar and Shandilya [69] performed the optimization of process parameters in magnetic field assisted powder mixed EDM (MFAPM-EDM) for cutting Al 6061, and compared the optimized performance of GA method with others. Danish et al [70] used the GWO approach to optimize the hydroxyapatite powder mixed electric discharge machining (HPM-EDM) process in order to improve modified surface characteristics, such as the recast layer thickness (RLT), of 316L stainless steel. The test demonstrated that the gray wolf optimizer's predicted solution sets are very accurate, with less than 10% inaccuracy.…”
Section: Single-objective Optimizationmentioning
confidence: 99%
“…Electrical discharge machining (EDM) is one of the practical solution methods for machining hard materials [1][2][3][4][5]. The complexity of EDM process led the researchers to take a lot of effort for finding the optimum process parameters [6][7][8][9][10][11][12]. The key point of research has been to develop an efficient system that leads to a higher material removal rate.…”
Section: Introductionmentioning
confidence: 99%